Uma análise das estratégias de manufatura adotadas por seis montadoras da indústria automobilística mundial - Gobbo, Simone Cristina de Oliveira [UNESP]; Rodrigues, José de Souza [UNESP]; Gobbo Júnior, José Alcides [UNESP]; Fusco, José Paulo Alves [UNESP] (My University, 2010)
The Brazilian automotive industry has undergone profound changes during the 90’s decade, as a consequence of the market opening up through the liberation of automobile imports. The exposure of the Brazilian domestic market to competition with imported products of high quality and lower prices indicated the need for significant changes in those auto industries operating in this country, with the intention of making them competitive. To achieve these objectives management and production concepts were adopted, such as: the just-in-time philosophy; lean manufacturing; outsourcing; reengineering and increasing the rate of automation in both production and management systems. These changes helped to increase productivity and, in turn, reduced the level of employment in the sector, especially in activities where the required qualification levels were low. Despite this modernization, the Brazilian companies have committed themselves to meet the specific needs of the Brazilian market. The objective of this paper is to analyze and present manufacturing strategies from six manufacturers of automotive vehicles: Toyota in Japan, Fiat in Italy, Volkswagen in Brazil and Germany and General Motors in the U.S. and Brazil. The predominant method of research was from reviewing relevant literature, whereas the empirical data was analyzed qualitatively. The article seeks to identify the manufacturing strategies adopted by manufacturers located in the above countries, electing one automotive manufacturer to represent each country. The research demonstrated that the processes for production of automobiles in four plants located in, the U.S. (GM); Italy (Fiat); Japan (Toyota) and Germany (VW) are similar to those adopted in Brazilian industrial plants of the same companies (GM and VW), with differences of operations only in the business strategies adopted by each of them.

O setor automotivo brasileiro passou por profundas transformações, durante a década de 90, devido à abertura do mercado pela liberação da importação de automóveis. A exposição do mercado interno brasileiro à competição com produtos importados, de alta qualidade e com preços menores, pressionou para que mudanças significativas fossem feitas nas indústrias instaladas no país, com objetivo de torná-las competitivas. Para que estes objetivos fossem alcançados, foram adotados conceitos de gestão e de produção, como a filosofia just in time, a fabricação enxuta, a terceirização, a reengenharia e a elevação do índice de automação da produção e do sistema gerencial. Estas mudanças ajudaram a elevar a produtividade e, em contrapartida, reduziram o nível de emprego no setor, especialmente em atividades, em que o nível de qualificação exigido era baixo. Apesar dessa modernização, as montadoras brasileiras empenharam-se em atender as especificidades do mercado brasileiro. O objetivo deste trabalho é analisar e apresentar as estratégias de manufatura de seis fabricantes de veículos automotores: Toyota, no Japão, Fiat, na Itália, Volkswagen, na Alemanha e no Brasil e General Motors, nos EUA e no Brasil. O método predominante de investigação foi a pesquisa bibliográfica, enquanto os dados empíricos foram analisados de forma qualitativa. O artigo procura identificar as estratégias de manufatura adotadas pelos fabricantes, localizados nos países acima citados, elegendo-se uma montadora para representar cada um deles. A pesquisa demonstrou que os processos de produção de veículos automotores, nas quatro plantas localizadas nos EUA (GM), Itália (Fiat), Japão (Toyota) e Alemanha (VW) são similares aos adotados nas plantas industriais brasileiras das mesmas empresas (GM e VW), com diferença das operações somente nas estratégias de negócios adotadas por cada uma delas.
Keywords: Automotive; Manufacturing strategy; Supply chains; Indústria automobilística; Estratégia de manufatura; Cadeias de fornecimento